(untitled) (Research, Society and Development, 2025)
Military logistics is a strategic pillar for the operational effectiveness of police-military corporations, especially in contexts such as the Military Police of Alagoas (PMAL), which faces geographic, budgetary, and public security challenges. This article aims to identify military logistics strategies applicable to PMAL through a systematic integrative review of 10 scientific articles (2010–2023), selected from SciELO and Google Scholar databases. The analysis focused on four themes: interinstitutional comparison, supply management, operational efficiency, and technological innovation. Results indicate the feasibility of models such as strategic centralization with regional supply centers (inspired by PMMG), adoption of performance metrics (e.g., response time), and integration of technologies (IoT, Big Data). Gradual outsourcing of non-essential services, under supervision, is also highlighted. The study concludes that adapting these practices, alongside academic partnerships and contingency plans, can optimize resources and strengthen public security in Alagoas.